2020
DOI: 10.3389/fmicb.2020.603818
|View full text |Cite
|
Sign up to set email alerts
|

Change of Endoglucanase Activity and Rumen Microbial Community During Biodegradation of Cellulose Using Rumen Microbiota

Abstract: Treatment with rumen microorganisms improves the methane fermentation of undegradable lignocellulosic biomass; however, the role of endoglucanase in lignocellulose digestion remains unclear. This study was conducted to investigate endoglucanases contributing to cellulose degradation during treatment with rumen microorganisms, using carboxymethyl cellulose (CMC) as a substrate. The rate of CMC degradation increased for the first 24 h of treatment. Zymogram analysis revealed that endoglucanases of 52 and 53 kDa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
4
14
0
Order By: Relevance
“…In this study, endo-glucanase was used as an important basis to judge the ability of cellulase. The results showed that liquid volume had a significant effect on endo-glucanase activity, and endo-glucanase was closely related to degradation rate, which is supported by previous works (Takizawa et al 2020 ; Wang et al 2004 ). This indicated that the lower dissolved oxygen environment caused by a higher liquid volume promote the activity of anaerobic lignocellulose degrading bacteria.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, endo-glucanase was used as an important basis to judge the ability of cellulase. The results showed that liquid volume had a significant effect on endo-glucanase activity, and endo-glucanase was closely related to degradation rate, which is supported by previous works (Takizawa et al 2020 ; Wang et al 2004 ). This indicated that the lower dissolved oxygen environment caused by a higher liquid volume promote the activity of anaerobic lignocellulose degrading bacteria.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, endo-glucanase was used as an important basis to judge the ability of cellulase. The results showed that liquid volume had a signi cant effect on endo-glucanase activity, and endo-glucanase was closely related to degradation rate, which is supported by previous works (Takizawa et al 2020;Wang et al 2004). This indicated that the lower dissolved oxygen environment caused by a higher liquid volume promote the activity of anaerobic lignocellulose degrading bacteria.…”
Section: Discussionsupporting
confidence: 84%
“…Five endoglucanases of the ruminant bacterial symbionts were detected, and their molecular weights were 42, 50, 52, 53, and 101 kDa [66]. Even though the 52 and 53 kDa EGs were more active compared to three other proteins, the authors did not classify these EGs into different GH families.…”
Section: Endo-endo Synergymentioning
confidence: 94%